Complications of emergency obstetric hysterectomy in Gujarat, India - Chauhan, Bhoomika R.; Patel, Aarti J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Emergency obstetric hysterectomy is defined as extirpation of uterus either at the time of cesarean section or following vaginal delivery, or within the puerperium to stop life threatening obstetric hemorrhage when all other measures fail. This study was conducted to study complications of emergency obstetric hysterectomy. Methods: Out of 28552 patients, 45 patients operated for Emergency obstetric hysterectomy in Vadilal Sarabhai Hospital of Ahmedabad, Gujarat; during May 2010 to October 2012 were included in the study. Complications of the procedures were identified and analyzed. Results: Hemorrhagic shock was the most common complication followed by fever. 15.55% (7 out 45) mothers were not saved even after the emergency obstetric hysterectomy. Conclusions: Improvising procedural skill and post-operative care can reduce the complications of emergency obstetric hysterectomy.